Android open source embedded system development using beagle board - Lee, Yu Yang. (2012)
This report represents the implementation of Android Open Source Development with the BeagleBoard-xM. This involves the porting of Android Operating System with USB Bluetooth add-on and to create Android applications which will interface with the board’s General Purpose Input / Output Port. In this project, Android applications for Home Automation System will be created to make use of such implementation. In the Home Automation System, users will be able control lightings and appliances at home on the Server-Side User Interface or on their mobile phones with wireless Bluetooth connectivity.